Challenged by Great Expectations? Examining Cross-Level Moderations and Curvilinearity in the Public Sector Job Demands–Resources Model. (June 2021) - Bauwens, Robin; Decramer, Adelien; Audenaert, Mieke
This article extends the job demands–resources model in the public sector by including (a) cross-level (moderation) effects of job demands and resources, (b) positive and nonlinear effects of job demands, and (c) vitality as a key work engagement concept. Data on expected contributions and developmental rewards in public university colleges (n = 65 teams and n = 219 employees) reveals that individual-level higher expected contributions are associated with higher performance, mediated by vitality. This mediation is stronger in the presence of more team-level developmental rewards, suggesting a cross-level moderated mediation. We find indications for curvilinear effects of expected contributions. Contrary to expectations, these effects do not show inverted U shapes, but rather exponential relations. Our results contribute to "bringing in a psychological perspective" in public administration and suggest that public leaders could apply the job demands–resources model as a practical tool and vitality as a metric to create healthy and effective work environments.